Androgenic anabolic steroid-induced liver injury: two case reports assessed for causality by the updated Roussel Uclaf Causality Assessment Method (RUCAM) score and a comprehensive review of the literature. Issue 1 (19th November 2020) - Abeles, Robin Daniel; Foxton, Matthew; Khan, Shahid; Goldin, Robert; Smith, Belinda; Thursz, Mark R; Verma, Suman
Abstract : Background: Anabolic androgenic steroids (AAS) usage is widespread and increasing. AAS drug-induced liver injury (DILI) is recognised but its clinical course and management is poorly described. We report 2 cases of AAS DILI with associated renal dysfunction, managed successfully with oral corticosteroids. Methods: A comprehensive review identified 50 further cases to characterise the clinical and biochemical course. Causality grading was calculated using the updated Roussel Uclaf Causality Assessment Method (RUCAM) score. Data are presented as median values. Results: The most common AAS taken was methyldrostanolone. Patients commonly present with jaundice and pruritus but may exhibit other constitutional symptoms. Patients presented 56 days after starting, and bilirubin peaked 28 days after stopping, AAS. Causality assessment was 'unlikely' in 1 (2%), 'possible' in 31 (60%) and 'probable' in 20 (38%). Peak values were: bilirubin 705 μmol/L, alanine transaminase 125 U/L, aspartate transaminase 71 U/L, alkaline phosphatase 262 U/L, gamma-glutamyl transferase 52 U/L, international normalised ratio 1.1. Liver biopsies showed 'bland' canalicular cholestasis. 43% of patients developed kidney injury (peak creatinine 225 μmol/L). Therapies included antipruritics, ursodeoxycholic acid and corticosteroids. No patients died or required liver transplantation. Conclusions: Physicians are likely to encounter AAS DILI. Causality assessment using the updated RUCAM should be performed but defining indications and proving efficacy for therapies remains challenging.